Sustainable Corrosion Protection of Aluminium Alloys – Life Cycle Assessment of Established and Innovative Coating Processes - Juergen M. Lackner; Reinhard Kaindl; Sara Carniello; Simon Chwatal; Max Stummer (Tehnički Glasnik)
Aluminium alloys are highly valued for their lightweight properties. However, their susceptibility to corrosion, particularly in chloride-containing environments, presents significant challenges especially when considering "green" sustainable processing routes. Applying ISO 14040 life cycle assessment (LCA) approach, traditional surface treatment techniques (anodization, conversion coatings, organic paints, plasma activated chemical vapour deposition in vacuum) are compared for the first time to innovative approaches such as Atmospheric Pressure Plasma Deposition (APPD). Although highly conservative assumptions are taken in the life cycle inventory, the greenhouse gas emissions of APPD are clearly lower than in the other technologies, especially because of the higher efficiency in feedstock use, the higher throughput, and the plasma-and air-supported oxidation of CH4, formed during dissociation of the silicon organic precursor. By achieving corrosion properties of cerium-doped APPD silicone coatings similar to the state-of-the-art and elimination of repainting as for organic paints, APPD is at the forefront of sustainable processing.